The relationship between academics’ strategic research agendas and their preferences for basic research, applied research, or experimental development - Santos, J. M. (2023)
In this study, we assess the association between academics’ research agendas and their preferences for basic research, applied research, or experimental development. Using a sample of Mexican academics working in some of the country’s most research-oriented universities, we identify three clusters. The largest is composed of applied research-oriented academics, the second largest is composed of basic research-oriented academics, and the smallest is composed of academics who engage in both basic and applied research, and experimental development. The strategic research agendas of the three clusters are distinguished from each other along four main dimensions: Divergence, Discovery, Mentor Influence, and Social Orientation. These findings show that strategic research agendas are associated with preferences for basic research, applied research, or experimental development, but only to some extent. We also extend the Multi-Dimensional Research Agendas Inventory – Revised, a widely used instrument for measuring strategic research agendas, by adding a new dimension, “Government,” and validating the instrument in a new context. We also make the scale available in Spanish for use by academics, practitioners, managers, and administrators in Spanish-speaking countries.